Comparison of Unmodulated Current Control Characteristics of Permanent Magnet Synchronous Motor - Muqorobin, Anwar; Irasari, Pudji; Taufik, Taufik (Research Centre for Electrical Power and Mechatronics, Indonesian Istitutes of Sciences, 2014)
This paper discusses comparison of unmodulated current controls in PMSM, more specifically, on-off, sliding mode, predictive and hybrid controls. The purpose of this study is to select the most appropriate control technique to be adopted. The comparison method is preceded by modeling the motor and entering the values of the motor parameters. PI control is used for speed control and zero d-axis current is employed. Furthermore, performing simulation for each type ofthe selected current controls and analyzing their responses in terms of dq and abc currents, q-axis current response with step reference, as well as THD. Simulation results show that the on-off control gives the best overall performance based on its abc-axis current ripple and THD at large load torque. The hybrid control shows the best response occurring only at the fastest transient time of q-axis current but its response exhibits bad qualities compared with other controls. The predictive control yields the best responses offering the smallest d-axis ripple current and THD at small load torque condition. The sliding mode control, however, does not exhibit any prominent performance compared to the others. Results presented in this paper further indicate that for the PMSM used in the simulation the most appropriate control is the predictive control.